Compulsory Jurisdiction in the Marriage Contract: A Comparative Jurisprudential Study - Salih, Khalid Mohamed (Journal of Legal and Political Studies, 2015)
This study (the mandate of forced marriage) is in terms of jurisprudence and law, which is defined as: the authority of the guardian to marry those who fall under his mandate without having the right to reject the objection.The fuqaha 'differed as to who this is proven to be a state, and it is more correct to prove the state to each of his wali, but without the authority to compel him to conclude the contract. Similarly, they differed in determining who is exercising the mandate of compulsion, following their differences in determining the state of coercion. To which they relied that there is no explicit evidence that can be used to determine the invocation of the mandate of coercion, and therefore the mandate of coercion has been proved.In order to determine the powers of the guardian, and to preserve the reconciliation of those who are loyal to them, the jurists put the mandate to force conditions. The most important of these are: The guardian must be a Muslim, male, adult, fair, free, fair, rational, halal. and anconalimum for pity. and to take into account the interests of the mullahs in marriage, because the actions of the obligatory guardian are vested in the interest, if they are not nullified.As for the position of the law on compulsory marriage, the Civil Code provided for the establishment of the mandate of coercion against young people, and the opinion that is opposed by many of the evidence and legal texts. As for the jurisdiction over adults, the Iraqi Personal Status Law - Paragraph 1 (c). Thus, the Iraqi Personal Status Law contradicts all the evidence of legality which provides for proving the state and role of the parents in the marriage contract. It contradicts the opinions and jurisprudence of all the Islamic sects who follow this matter, as well as its general provisions and basic principles which are supposed to be derived from Islamic law.
Keywords: marriage; jurisprudence; coercion; compel